PRÁTICAS CRIMINALIZADAS EM CASAS COMERCIAIS (COMARCA DE MALLET/PR: 1950-1978) - Soczek, Leonardo Henrique Lopes (2018)
This dissertation aims to analyze the practices criminalized in commercial houses registered in the criminal cases of the Comarca de Mallet / PR, constituted by the municipalities of Mallet and Paulo Frontin and their respective districts, between 1950 and 1978. Containing documents investigations and criminal cases since 1913, the collection provided by CEDOC / I demonstrates the predominance of cases involving commercial houses from the 1950s, and a significant drop after the end of the 1970s. Through this time cut, it was possible to analyze the largest number of cases and interpret the meanings of these criminalized practices attributed by the local judiciary and in the narratives elaborated by the accused, victims and witnesses of the cases. In order to do so, we base ourselves on notions about the Certeunian concepts of place, practiced spaces, strategies and tactics, and on the Foucaultian concepts of power, discourse, truth, and the processes of subjectivation and objectification. These conceptual notions make possible an interpretative approach to the quantitative and qualitative data of the sources. Located in the southeastern region of the State of Paraná, Mallet was marked by Slavic immigration and developed in a large rural area and a restricted urban center. In the midst of the prevailing agricultural development, the formation of commercial houses characterized as warehouses, bars, taverns and the like, represented the main private commercial and sociability spaces in the beginning and middle of the XX century. The practices of the space were diverse, so that some were criminalized and prosecuted by the local judiciary that acquitted the majority of the accused. The cases also demonstrated the existence of other practices that constituted other spaces, such as masculinities, virilities, honor defense and drunkenness that, together with the different practices of violence, made up the majority of practices in the commercial houses of the 1950s until the late 1970s.